Early Diagnosis and Prompt Treatment of Severe Stenosis in The Proximal Left Anterior Descending Coronary Artery (Wellens’ Syndrome) - Har Rawishwar Singh Dhilion; Haikal; Vireza Pratama; Agus Harsoyo; Bambang Pamungkas (PT Kalbe Farma Tbk., 2019)
The electrocardiography misinterpretation occurs in 20-40% of misdiagnosed myocardial infarction cases. Wellens' syndrome is a typical T-wave finding that shows severe stenosis in the proximal of left anterior descending (LAD) artery, leading to extensive anterior myocardial infarction within days. Cardiac stress tests should not be performed in this condition. Prognosis is fair when identified early and proper coronary intervention was immediately performed. Kesalahan interpretasi elektrokardiografi terjadi pada 20-40% kasus infark miokard yang salah terdiagnosis. Sindrom Wellens merupakan temuan gelombang-T khas yang menunjukkan stenosis berat di arteri turun anterior kiri (LAD) proksimal, dapat menyebabkan infark miokard anterior luas dalam beberapa hari. Tes stres jantung tidak boleh dilakukan dalam kondisi ini. Kebanyakan pasien dapat membaik jika teridentifikasi dini dan intervensi koroner yang tepat segera dilakukan.